Isolation of Mycoplasma bovis from broiler chickens in Turkey - Ongor, Hasan; Kalin, Recep; Karahan, Murat; Cetinkaya, Burhan; McAuliffe, Laura; Nicholas, Robin A. J. (Taylor & Francis Ltd, 2008)
Mycoplasma bovis normally affects cattle, in which it causes pneumonia in calves, mastitis, arthritis and other diseases. In the present article we report the isolation of this bovine pathogen from the tracheas of broiler chickens with no clinical signs. The most probable source of infection was the cattle herd sharing the farm with the chickens.
Keywords: Pcr